Haruskah Aku Bekerja? (Studi Fenomenologi Keputusan Bekerja pada Pemuda Penyandang Disabilitas di Empat Wilayah di Jawa Tengah) - Fuji Riang Prastowo; Irmaningsih Pudyastuti; Bangkit Rygen Dewantara (Jurnal Studi Pemuda, 2018)
Coping is one form of strategy to deal with stigma and all forms of social pressure that lead obstacles to the growth of young people with disabilities. In this case, coping can be interpreted as a person's effort to overcome the obstacles experienced with certain strategies.  In the context of persons with disabilities, the community often views persons with disabilities as a weak marginal group as being dependant to family so that there is no demand to work like humans in general. In addition, there are little opportunity for them to work in the formal sectors causes many of them to be coping with their own efforts for being independent. Therefore, this paper seeks to explore more about coping strategies carried out by youth with disabilities to decide to work. This paper comes from the results of field research with phenomenological qualitative methods in May-June 2018 through FGD and in-depth interviews conducted in four regions in Central Java Province namely Demak Regency, Semarang City, Semarang Regency, and Boyolali Regency. The results of the study indicate that the decision to work or not work from young people with disabilities comes from the response of external factors. Coping is then born into three level : the appraisal-focused level, emotions (the emotion-focused), and actions (problem-focused), which are not linear but can occur differently for each individual depending on the context of growth and development.